The Drosophila p70[s6k] homolog exhibits conserved regulatory elements and rapamycin sensitivity. - Stewart, M.J.; Berry, C.O.; Zilberman, F.; Thomas, G.; Kozma, S.C. (Proceedings of the National Academy of Sciences of the United States of America, 1996)
The protein p70s6k/p85s6k lies on a mitogen-stimulated signaling pathway and plays a key role in G1 progression of the cell cycle. Activation of this enzyme is mediated by a complex set of phosphorylation events, which has largely contributed to the difficulty in identifying the upstream kinases that mediate p70s6k activation. Genetics has proved a powerful complementary approach for such problems, providing an alternative means to identify components of signaling cascades and their functional end targets. As a first step toward implementing such an approach, we have cloned cDNAs encoding the Drosophila melanogaster p70s6k homolog (Dp70s6k). Dp70s6k is encoded by a single gene, which generates three mRNA transcripts and exhibits an overall identity of 78% in the catalytic domain with its mammalian counterpart. Importantly, this high identity extends beyond the catalytic domain to the N terminus, linker region, and the autoinhibitory domain. Furthermore, all the critical phosphorylation sites required for mammalian p70s6k activation are conserved within these same domains of Dp70s6k. Chief amongst these conserved sites are those associated with the selective rapamycin-induced p70s6k dephosphorylation and inactivation. Consistent with this observation, analysis of total S6 kinase activity in fractionated Drosophila Schneider line 2 cell extracts reveals two peaks of activity, only one of which is rapamycin sensitive. By employing a monospecific polyclonal antibody generated against Dp70s6k, we show that the cloned DP70s6k cDNA has identity with only the rapamycin sensitive peak, suggesting that this biological system would be useful in determining not only the mechanism of p70s6k activation, but also in elucidating the mechanism by which rapamycin acts to inhibit cell growth.